1998
DOI: 10.1007/s001250050946
|View full text |Cite
|
Sign up to set email alerts
|

Insulin resistance characterizes glucose uptake in skeletal muscle but not in the heart in NIDDM

Abstract: Signs or symptoms of macrovascular disease are frequently found even prior to the development of noninsulin-dependent diabetes mellitus (NIDDM) [1]. This suggests that coronary heart disease (CHD) and NIDDM share a pathophysiologic feature, which predisposes to both diseases. Classic risk factors such as serum cholesterol, age, gender, hypertension and smoking explain only a fraction of the 2±4-fold increase in cardiovascular mortality in patients with NIDDM [1,2]. Insulin resistance, usually measured by qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
90
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(95 citation statements)
references
References 31 publications
5
90
0
Order By: Relevance
“…The impairment of insulin-mediated myocardial glucose disposal reported by these authors in patients with type 2 diabetes ranges between 22 and 39%. Utriainen et al (13), conversely, found comparable rates of MGU in patients with type 2 diabetes and healthy control subjects under conditions of supraphysiological insulinization (200 mU ⅐ min Ϫ1 ⅐ m Ϫ2 insulin clamp) and after an overnight insulin infusion in the patients with diabetes alone. Although we cannot exclude that pharmacological insulin stimulation might overcome the defect observed in our patients, the present study clearly demonstrates that cardiac glucose uptake in response to physiological hyperinsulinemia is defective in type 2 diabetes.…”
Section: Fig 2 Direct Relationship Between Myocardial Muscle (Top) Andmentioning
confidence: 89%
See 2 more Smart Citations
“…The impairment of insulin-mediated myocardial glucose disposal reported by these authors in patients with type 2 diabetes ranges between 22 and 39%. Utriainen et al (13), conversely, found comparable rates of MGU in patients with type 2 diabetes and healthy control subjects under conditions of supraphysiological insulinization (200 mU ⅐ min Ϫ1 ⅐ m Ϫ2 insulin clamp) and after an overnight insulin infusion in the patients with diabetes alone. Although we cannot exclude that pharmacological insulin stimulation might overcome the defect observed in our patients, the present study clearly demonstrates that cardiac glucose uptake in response to physiological hyperinsulinemia is defective in type 2 diabetes.…”
Section: Fig 2 Direct Relationship Between Myocardial Muscle (Top) Andmentioning
confidence: 89%
“…Choice of the arm muscle instead of the leg, as used by other authors (7,11,13), was uniquely based on the advantage that this muscle lies within the same field of view as the myocardium and can be scanned simultaneously. Data analysis.…”
Section: Regions Of Interestmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous evidence also indicates that myocardial insulin resistance might be overcome by raising hyperinsulinaemia to supraphysiological concentrations in patients with uncomplicated Type II diabetes [18]. Although coronary artery disease (CAD) can be associated with myocardial insulin resistance [11] and sub-clinical CAD cannot be completely excluded in our patients, our inclusion criteria rule against this possibility; nevertheless, sub-clinical cardiovascular disease has not been related with myocardial insulin resistance.…”
Section: Discussionmentioning
confidence: 78%
“…Furthermore, Yokoyama et al also reported that MGU was similar in both hypertensive T2DM and controls despite significantly reduced SMGU and whole body glucose disposal rates in the former indicating an existence of insulin resisatnce in skeletal muscle and whole body but not in the heart in patients with T2DM and hypertension [18]. Moreover, myocardial insulin resistance was not observed when using very high insulin doses for insulin clamping (about 10 times higher than usual) while insulin resistance in the whole body and skeletal muscle was still present [19]. Consistent with this discrepancy, preserved MGU in response to insulin clamping under chronic use of sulfonylurea drugs in T2DM has been also reported [20].…”
Section: Main Part Of Review and Discussionmentioning
confidence: 99%